(untitled) (Journal of Informatics Education and Research, 2025)
This study investigates the influence of Psychological Capital (PsyCap)—consisting of self-efficacy, hope, resilience, and optimism—on teacher performance in private universities. It further explores how PsyCap contributes to job involvement, work engagement, professional resilience, and academic effectiveness. Drawing on the Conservation of Resources (COR) theory, the research examines the mediating roles of work engagement and emotions, and the moderating impact of gender. The study is supported by empirical findings from various national and international studies, which confirm that high PsyCap levels enhance emotional well-being, organizational commitment, and quality of work life, leading to improved teacher performance. The results have practical implications for academic institutions aiming to foster teacher development and performance through PsyCap-enhancing strategies.